The multidisciplinary management of HER2-positive breast cancer brain metastases: from new biological insights to future therapeutic options - von Arx, Claudia; Calderaio, Claudia; Calabrese, Alessandra; Marciano, Benedetta; Martinelli, Claudia; Di Lauro, Vincenzo; Cerillo, Ivana; Cianniello, Daniela; De Laurentiis, Michelino (Frontiers in Oncology, 2024)
The advent and success of new drugs for treating HER2-positive metastatic breast cancer has led to a constant improvement in disease and progression-free survival as well as overall survival. Despite these advantages, the overall survival and quality of life of patients with HER2-positive breast cancer brain metastases are significantly worse than the ones of patients with HER2-positive breast cancer metastases outside the brain. For this reason, prevention and treatment of brain metastasis remain a major clinical challenge and the keys to further improving the clinical and survival outcomes of HER2-positive breast cancer patients. This review discusses the etiopathogenesis of brain metastasis, the currently available treatments, and the future perspective on new treatment strategies and diagnostic tools.